Regenerative Medicine for the Treatment of Ischemic Heart Disease; Status and Future Perspectives - Arjmand, Babak; Abedi, Mina; Arabi, Maryam; Alavi-Moghadam, Sepideh; Rezaei-Tavirani, Mostafa; Hadavandkhani, Mahdieh; Tayanloo-Beik, Akram; Kordi, Ramin; Roudsari, Peyvand Parhizkar; Larijani, Bagher (Frontiers in Cell and Developmental Biology, 2021)
Cardiovascular disease is now the leading cause of adult death in the whole world. According to new estimates from the World Health Organization, myocardial infarction (MI) is responsible for 4 out of every 5 deaths due to cardiovascular disease. Conventional treatments of MI are taking aspirin and nitroglycerin as intermediate treatments, taking aspirin, and injecting antithrombotic agents within the first 3 hours after MI along with coronary artery bypass grafting and percutaneous coronary intervention as long term treatments. Since none of these interventions will fully regenerate the infarcted myocardium, the value of pursuing more innovative therapeutic approaches is highlighted. Regenerative medicine is an innovative interdisciplinary method for rebuilding, replacing, or repairing the missed part of different organs in the body, as similar as possible to the primary structure. In recent years, regenerative medicine has been widely utilized as a treatment for ischemic heart disease (one of the most fatal factors around the world) to repair the lost part of the heart by using stem cells. Here, development of using mesenchymal stem cells causes a breakthrough in the treatment of different cardiovascular diseases. They are easily obtainable from different sources, expanded and enriched easily, utilizing with no need for immunosuppressing agents before transplantation, and less possible genetic abnormality is accompanied with them through multiple passages. Indeed, the production of new cardiomyocytes can result from the transplantation of different types of stem cells. Accordingly, due to its remarkable benefits, stem cell therapy received attention in this field. It provides a drug-free and surgical treatment for the patients as well as more safety and feasibility in cardiac repair. Although different clinical trials reported promising benefits of stem cell therapy, there is still uncertainty about its mechanism of action. Accordingly, conducting different preclinical and clinical studies seems important to explore the exact mechanism of action of the cells. Herein, after reviewing the pathophysiology of MI, the role of tissue regeneration is addressed using various materials, including different types of stem cells. Eventually, some appropriate data is provided about the importance of ethical problems, which leads to the scientific method's future perspectives.